Improving Part-of-Speech Tagging Accuracy for Croatian by Morphological Analysis - Agić, Željko; Tadić, Marko; Dovedan Han, Zdravko (2008)
This paper investigates several methods of combining a second order hidden Markov model part-of-speech (morphosyntactic) tagger and a high-coverage inflectional lexicon for Croatian. Our primary motivation was to improve tagging accuracy of Croatian texts by using our newly-developed tagger CroTag, currently in beta-version. We also wanted to compare its tagging results – both standalone and utilizing the morphological lexicon – to the ones previously described in (Agić and Tadić 2006), provided by the TnT statistical tagger which we used as a reference point having in mind that both implement the same tagging procedure. At the beginning we explain the basic idea behind the experiment, its motivation and importance from the perspective of processing the Croatian language. We also describe tools – namely tagger and lexicon – and language resources used in the experiment, including their implementation method and input/output format details that were of importance. With the basics presented, we describe in theory four possible methods of combining these resources and tools with respect to their operating paradigm, input and production capabilities and then put these ideas to test using the F-measure evaluation framework. Results are then discussed in detail and conclusions and future work plans are presented.
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG